2012
DOI: 10.1038/ijo.2012.57
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the obesity-associated gene variants within the entire FTO gene by ultra-deep targeted sequencing in obese and lean children

Abstract: Background:The Fat mass and obesity-associated gene (FTO) was the first gene reliably associated with body mass index in genome-wide association studies on a population level. At present, the genetic variations within the FTO gene are still the common variants that have the largest influence on body mass index.Methods:In the current study, we amplified the entire FTO gene, in total 412 Kbp, in over 200 long-range PCR fragments from each individual, from 524 severely obese and 527 lean Swedish children, and seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 32 publications
0
31
1
1
Order By: Relevance
“…But our study showed that rs62048402 had a lower odds ratio (OR = 1.259, 95% CI = 1.016-1.560, P = 0.035) than rs9939609 (OR = 1.322, 95% CI = 1.067-1.637, P = 0.011). In Sällman Almén's study (9), rs9939609 and rs62048402 was in a linkage disequilibrium (LD) with r 2 value of 0.87 among Swedish children. The r 2 value was 0.96 in our Chinese population, indicating LD of the two FTO SNPs among Chinese population was stronger than that of European population.…”
Section: Association Of Eight Variants With Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…But our study showed that rs62048402 had a lower odds ratio (OR = 1.259, 95% CI = 1.016-1.560, P = 0.035) than rs9939609 (OR = 1.322, 95% CI = 1.067-1.637, P = 0.011). In Sällman Almén's study (9), rs9939609 and rs62048402 was in a linkage disequilibrium (LD) with r 2 value of 0.87 among Swedish children. The r 2 value was 0.96 in our Chinese population, indicating LD of the two FTO SNPs among Chinese population was stronger than that of European population.…”
Section: Association Of Eight Variants With Obesitymentioning
confidence: 99%
“…All the two SNPs were within intron 1 of FTO (15). Sällman et al (9) found that the intron 1 is the only region within FTO associated with obesity, and reported that rs62048402 (OR = 1.35, 95% CI = 1.13-1.60, P < 0.0007) had a stronger association with obesity than SNP rs9939609 (OR = 1.25, 95% CI = 1.05-1.48, P < 0.012). But our study showed that rs62048402 had a lower odds ratio (OR = 1.259, 95% CI = 1.016-1.560, P = 0.035) than rs9939609 (OR = 1.322, 95% CI = 1.067-1.637, P = 0.011).…”
Section: Association Of Eight Variants With Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently however, results of a new study have been released in which the entire FTO gene in total 412 Kbp has been amplified in a group of 524 morbid obese and 527 lean Swedish children [19]. This is the first comprehensive variation map of the FTO gene, including both SNPs and small indels (small deletions and insertions), using new generation sequencing of pooled DNA -massive parallel sequencing (SOLiD).…”
Section: Fto and Obesity In Different Ethnic Groupsmentioning
confidence: 99%
“…This was confirmed in a recent study on a Latvian population [18] where SNPs rs62048402, rs9939609 and rs7561317 were associated with higher BMI with p-values of 0.0036, 0.0069 and 0.015 respectively. The four top obesity-associated SNPs in a study by Almen et al [19], with rs62048402 being the strongest one, lie within the potential regulatory region of intron one. Some transcription factors, such as the glucocorticosteroid receptor, bind there and this is the only known functional region of the comprehensive FTO map which may potentially explain the pathomechanism of related obesity.…”
Section: Fto and Obesity In Different Ethnic Groupsmentioning
confidence: 99%